Analisis Kinerja Keuangan Pengelolaan Alokasi Dana Desa Berdasarkan Rasio Efektivitas, Rasio Efisiensi Dan Rasio Pertumbuhan Pada Pemerintah Desa Kaliboto Kabupaten Blitar Periode 2019-2021 - Alyumna Asfiatul Hikmah; Edi Murdiyanto; Zulfia Rahmawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Financial performance analysis is carried out by comparing the results achieved from one period with another. In this case, the ratios used by the author in this research are the effectiveness ratio, efficiency ratio and growth ratio. This ratio is used to provide an overview of information regarding financial performance over the last three years (2019-2021). This research uses quantitative methods because the data collected is in the form of figures obtained from the 2019-2021 APBDes Realization Report. The data used in this research is a time series. The results of this research show that the effectiveness ratio of the Kaliboto Village government from 2019 to 2020 has very effective performance. The efficiency ratio of the Kaliboto Village government in 2019 to 2021 experienced increases and decreases. The growth ratio in 2019 increased by 7.17%, then descreades in 2020 by 1.45%, but decreased in 2021, namely -10.07%.